RASIO TULANGAN OPTIMUM PADA BAJA TULANGAN BJTP DAN BJTD BALOK EMPAT PERSEGI PANJANG TULANGAN TUNGGAL - Eri Setia Romadhon (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
What is the optimum reinforcement ratio that can be achieved for plain reinforcing steel (BJTP) and deformed reinforcing steel (BJTD) to obtain the maximum moment of resistance in a single reinforced rectangular beam? The optimum reinforcement ratio is achieved when the moment of resistance reaches the maximum value for a certain optimum reinforcement ratio value. By knowing the optimum reinforcement ratio, it will be very easy to make the most efficient increase in beam strength. This study uses a case study of rectangular beams with various dimensions which are often used in high-rise building projects. At the moment of maximum resistance for single-reinforced rectangular beams, the optimum reinforcement ratio for BJTP steel is 0.0885 and BJTDreinforcing steel is 0.0531.